Apoptosis index of cerebrum and cerebellum neuronal cells in Rattus norvegicus neonates born from mothers treated with 50% food restriction during gestation - Andita Hapsari; Hermanto Tri Joewono; Widjiati Widjiati (Majalah Obstetri dan Ginekologi, 2018)
Objective: To analyze the difference of neuronal apoptotic index on Rattus norvegicus offspring in cerebrum and cerebellum between food restriction 50% group and control.Materials and Methods: An analytical experimental study with single blind randomized post test only control group using animals subjects Rattus norvegicus. This study was conducted at animal laboratory, Veterinary Faculty, Universitas Airlangga. Animal subjects were divided into food restriction 50% group and control. The apoptotic index was analyzed using comparison test, with significancy p<0.05.Results: There was significant difference of neuronal apoptotic index on Rattus norvegicus offspring between FR 50% group and control in cerebrum with p= 0.002 (mean 6,12±3,51 in FR 50% group, 2,81±2,16 in control group), and cerebellum with p= 0.026 (mean 5,56±3,03 in FR group, 3,43±2,58 in control group).Conclusions: Food restriction 50% during gestation has signifi-cant influence on neuronal apoptotic index in cerebrum and cerebellum of Rattus norvegicus offspring.